The impact of web-based and face-to-face simulation education programs on nurses' response to patient deterioration: A multi-site interrupted time series study. (July 2021) - Kinsman, Leigh; Cooper, Simon; Champion, Robert; Kim, Jeong-Ah; Boyle, Jayne; Cameron, Amanda; Cant, Robyn P.; Chung, Catherine; Connell, Cliff; Evans, Lisa; McInnes, Denise; McKay, Angela; et al.
Abstract: Background: Nurses' response to patient deterioration in acute hospital wards is a priority issue. Simulation education programs improve nurses' knowledge and confidence, but the translation into better care is largely unknown for both web based (WB) and face to face (F2F) simulation programs. Aim: To measure the impact of simulation education on nurses' response to patient deterioration in acute medical ward settings, and to compare the impact of WB and F2F versions. Design: An interrupted time series, non-randomised trial across four medical wards in Victoria, Australia. Wards were allocated to either web-based or face-to-face versions of the same simulation program, FIRST2ACT. Interrupted time series measurement for six fortnights both before and after the intervention were used to measure and compare responses to deterioration. Responses to patient deterioration were extracted from medical records and grouped into outcomes for escalation (e.g. initiation of clinical review), assessment and observation (e.g. increased recording of vital signs, conscious state and pain scores) and clinical interventions (e.g. oxygen administration). Results: 126 nurses (89%) participated across the four wards. 946 patient records (506 in the F2F; 440 in the WB group) were included in analyses. There were significant and sustained improvements between pre and post samples in outcomes for escalation (13.0% to 28.8%; p = 0.000) and assessment and observation (conscious state recorded increased from 91.1% to 100%; p = 0.000, and pain score recorded increased from 97.8% to 99.8%; p = 0.000). There were no differences between the web-based and face-to-face groups except in appropriate oxygen application which increased by 7.7% in the F2F group and decreased by 11.8% in the WB group ( p = 0.046). Conclusions: There was a significant improvement in nurses' response to patient deterioration following both versions of simulation, indicating that both have a role to play in supporting nurses' response to patient deterioration.